+0  
 
0
826
1
avatar

3(2x+1)(-x+3)-(2x+5)2=-[-{-3(x+5) }+10x 2].

Guest Mar 22, 2017
 #1
avatar+7153 
+3

Alright why not I'll try this one...

Assuming this is the question:

3(2x+1)(-x+3) - (2x+5)2 = -[ - { -3(x+5) } + 10x2]

 

(6x+3)(-x+3) - (2x+5)(2x+5) = -[ - { -3x-15 } + 10x2]

 

(-6x2 + 15x + 9) - (4x2 + 20x + 25) = -[ 3x + 15 + 10x2]

 

-6x2 + 15x + 9 - 4x2 - 20x - 25 = -3x - 15 - 10x2

 

-10x2 - 5x - 16 = -3x - 15 - 10x2

 

-5x - 16 = -3x - 15

 

-5x = -3x + 1

 

-2x = 1

 

x = -1/2

hectictar  Mar 22, 2017

10 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.